Efecto del sobrepeso sobre la capacitación y reacción acrosomal en espermatozoides de conejo Nueva Zelanda blanco - Ruiz Valderrama, Lorena (Universidad Autónoma Metropolitana, 2014)
The target for the present study was to evaluate the effect of everweight in semina parameters and physiological processes such as sperm capacitation and acrosome reaction in vitro in White New Zealand rabbit sperm. The provided caloric diet induced overweight in the experimental group, presenting a rate of 18.5% more weight tan the control group. When semen quality was evaluated, it can observed that the masal motility was not affected by overweight, because the values in the two groups were 2 and 3, which were considered the máximum values of masal motility and good seminal quality; the sperm viability was not altered, the overweight group had a tendency to decrease at a rate of 60%, against 75% of the normal weight group. The progressive motility was not altered by overweight. The overweight group was similar to normal weight group, 70% and 65% percentage respectively; sperm concentration was between 400 and 500 million sperm per milliliter. Seminal volumen showed slight differences, 0.6ml and 0.7ml respectively. The sperm morphology was affected by overweight. The abnormalities percentage was 19.5±4.9 in control group and 35±13.3 in overweight group. Sperm capacitation is altered because of overweight, the percentage of capacitated sperm decreased; the value in the normal weight group was 25% and 15% overweight. The spontaneous acrosome reaction increase escessively because normal weight group was 39.2% and induced acrosome reaction decreased in overweight group 25.1%. Which lead us to conclude that overweight in New Zealand rabbits increase the abnormalities percentage and affect the capacitation and acrosome reaction.; El objetivo de este trabajo fue evaluar el efecto del sobrepeso en los parámetros espermatobioscópicos y en procesos fisiológicos como la capacitación espermática y la reacción acrosomal in vitro en espermatozoides de conejo Nueva Zelanda blanco. La dieta hipercalórica proporcionada indujo un estado de sobrepeso al grupo experimental, al presentar un aumento de peso del 18.5% más comparado con el grupo control. Al evaluar la calidad seminal se pudo observar que no fue afectada la movilidad masal, que fue de 2 y 3 (en escala de: 0 a 3), lo que se consideró valores máximos de movilidad masal y de buena calidad seminal; la viabilidad en el grupo con sobrepeso fue del 60 y del 75% en el de peso normal; la movilidad progresiva, el grupo de sobrepeso no presentó diferencia significativa con el grupo de peso normal (7vs 65%, respectivamente); la concentración espermática fue de 400 vs 500 X10⁶ espermatozoides/ml. El volumen seminal mostró ligeros cambios (0.6 y 0.7ml respectivamente). El sobrepeso afecto la morfología espermática. El porcentaje de anormalidades en el grupo normopeso fue de 19.5±4.9 y 35±13.3 en sobrepeso. La capacitación espermática in vitro disminuyo a causa del sobrepeso, observándose 25% en el grupo normopeso vs15% en el grupo testigo. La variable que más se modifico fue la reacción acrosomal espontánea, que aumento hasta 39.2% mientras que la reacción acrosomal inducida disminuyó en el grupo de sobrepeso 25.1% siendo las de los testigos 40.5%. En conclusión, el sobrepeso en conejos Nueva Zelanda aumenta el porcentaje de anormalidades, además de que afecta los procesos de capacitación y reacción acrosomal.